2022
DOI: 10.1158/2159-8290.cd-22-0210
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic rRNA Ribomethylome Drives Stemness in Acute Myeloid Leukemia

Abstract: The development and regulation of malignant self-renewal remains an unresolved issue. Here, we provide biochemical, genetic, and functional evidence that dynamics in ribosomal RNA (rRNA) 2'-O-methylation regulate leukemia stem cell (LSC) activity in vivo. A comprehensive analysis of the rRNA 2'-O-methylation landscape of 94 acute myeloid leukemia (AML) patients revealed dynamic 2'-O-methylation specifically at exterior sites of ribosomes. rRNA 2'-O-methylation pattern is closely associated with AML development… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 80 publications
(105 reference statements)
0
23
0
Order By: Relevance
“…Dysfunction on any one of the three snoRNAs: SNORD26, SNORD44, or SNORD78 results in severe morphological abnormalities and embryonic death (Higa-Nakamine et al, 2012). Through a thorough analysis of the rRNA Nm landscape from 94 patients with AML, recent studies also confirmed the plasticity of rRNA Nm that shifts protein translation toward a leukemia stem cell phenotype (Zhou et al, 2023) (Figure 2C). It is interesting to note that in a population of ribosomes, the amounts of modification at the various 2-O methylatable sites are not necessarily the same, but the center of ribosomal subunits frequently contains fully ribomethylated regions.…”
Section: '-O-methylation (Nm)mentioning
confidence: 86%
“…Dysfunction on any one of the three snoRNAs: SNORD26, SNORD44, or SNORD78 results in severe morphological abnormalities and embryonic death (Higa-Nakamine et al, 2012). Through a thorough analysis of the rRNA Nm landscape from 94 patients with AML, recent studies also confirmed the plasticity of rRNA Nm that shifts protein translation toward a leukemia stem cell phenotype (Zhou et al, 2023) (Figure 2C). It is interesting to note that in a population of ribosomes, the amounts of modification at the various 2-O methylatable sites are not necessarily the same, but the center of ribosomal subunits frequently contains fully ribomethylated regions.…”
Section: '-O-methylation (Nm)mentioning
confidence: 86%
“…13 Dysregulation of the RNA-guided rRNA 2′methylation machinery has been linked to various human diseases. 14 RNA-guided 2′-O-methylation is also implicated in both major class (U1, U2, U4, U5, and U6) and minor class (U11, U12, U4atac and U6atac) spliceosomal snRNAs, and 18 box C/ D snoRNAs or scaRNAs are involved in modifying these spliceosomal snRNAs. This 2′-O-methylation in snRNAs is crucial for spliceosome assembly, ensuring proper interaction with proteins and other snRNAs as well as RNA splicing.…”
Section: Rna-guided 2′-o-methylationmentioning
confidence: 99%
“…In addition, the methylated reader protein TAR RNA-binding protein (TRBP) binds to the methyltransferase FtsJ RNA 2’-O-methyltransferase 3 (FTSJ3) to form a TRBP-FTSJ3 complex, which induces 2′-O-Me [ 89 ]. Fibrillarin (FBL) is also a 2’-O-methyltransferase that can form a small nucleolar ribonucleoproteins (snoRNPs) with three other proteins and snoRNA for specific rRNA modifications [ 90 ]. Ψ is produced by the isomerization of uridine, catalyzed by pseudouridine synthase (PUS).…”
Section: Rna Epigenetics Mechanismsmentioning
confidence: 99%